(untitled) (Journal of Pathology of Nepal, 2012)
Background: Pure mucinous carcinoma is a rare histologic type of mammary neoplasm and may exist as mixed mucinous-ductal carcinoma. This study aims to describe fine needle aspiration cytology features of mucinous carcinoma of breast diagnosed in Tribhuvan University Teaching Hospital, Nepal over the period of 2 years and to correlate with histological findings. Materials and Methods: There were a total of 8 cases of mucinous carcinoma of breast, diagnosed on fine needle aspiration cytology in TUTH during the period from April 2010 to March 2012. The patient’s age, laterality of involvement, fine needle aspiration cytology features, gross and histological findings, type of surgery performed and tumor size were evaluated. Fine needle aspiration cytology smears were evaluated for cellularity, amount of mucin, chicken-wire vasculature and nuclear atypia. Results: Fine needle aspiration cytology provided a pre-operative diagnosis of mucinous carcinoma in 5 cases and mixed mucinous carcinoma-invasive ductal carcinoma in 3 cases. Histological examination showed pure mucinous carcinoma in 3 cases, mixed mucinous carcinoma-invasive ductal carcinoma in 4 cases and mixed cribriform carcinoma and ductal carcinoma in 1 case. Conclusion: Mucinous carcinoma may appear clinically and radiologically benign and fine needle aspiration cytology plays important role in the correct pre-operative diagnosis. Significant nuclear pleomorphism and necrosis, in addition to extracellular mucin suggests mixed mucinous carcinomainvasive ductal carcinoma. Journal of Pathology of Nepal (2012) Vol. 2, 285-288 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6879